Plug-in battery electric vehicle : lighting system - Wong, Bjorn Wing Tjoi (2019)
Over the years, global warming has been a serious environmental problem affecting both our ecosystem and health. Automobile emission is one of the main contributing factors of global warming. Although newer vehicles are built-in with a catalysis convertor, harmful gases such as carbon dioxide, carbon monoxide and nitrogen dioxide are still being emitted into the environment. Thus, research and development for alternative source of power used in automobiles is required to reduce harmful emission. One alternative source of power is the use of battery to drive the vehicle via an electrical motor. Battery Electric Vehicle (BEV) aims to create a cleaner and greener future for better transportation in Singapore. The author is a member of a team of 3 Final Year Project (FYP) student taking on the next phase of project from previous FYP students. The objective is to implement a lighting system for the vehicle body shell. The lighting system consist of 2 headlamps, 2 turn signal lamps at the front, 2 brake lamps, 2 turn signal lamps and 2 reversing lamps. The primary role of the author is to design and fabricate the light clusters and mount securely onto the aluminium shell using standard parts, 3D printing or plastic bending processes.